Assessing the Compatibility of Menatetrenone with Excipients: A Spectroscopic Approach and Implication in Drug Formulation Development - Singh, Widhilika; Kushwaha, Poonam; Kushwaha, Shom Prakash (Drug Research, 2024)
An experiment was conducted to evaluate the compatibility of menatetrenone with selected pharmaceutical excipients. Fourier Transform Infrared Spectroscopy (FTIR) was used to assess drug-excipient compatibility. The present research systematically investigates the FTIR spectrum of each chemical compound separately and their physical blends, analyzing for possible shifts, alterations or novel peak that may indicate chemical interactions. This study aims to utilize spectral data interpretation to detect potential compatibility problems that may occur while design and production of menatetrenone containing dosage forms ensuring their increased stability and effectiveness. The FTIR results demonstrated that all the pharmaceutical excipients were compatible with menatetrenone. In conclusion, the compatibility of pharmaceutical excipients with menatetrenone was successfully assessed using FTIR that will aid in future design of formulations containing menatetrenone as therapeutic moiety.
Keywords: menatetrenone; fourier transform infrared spectroscopy; compatibility study; vitamin K2; menaquinone-4 analysis; drug-excipient interaction